Insights for Undergraduates Seeking an Advanced Degree in Wildlife and Fisheries Sciences. Issue 11 (9th November 2013) - Kaemingk, Mark A.; Dembkowski, Daniel J.; Meyer, Hilary A.; Gigliotti, Larry M.
ABSTRACT: In today's job market, having a successful career in the fisheries and wildlife sciences is becoming more dependent on obtaining an advanced degree. As a result, competition for getting accepted into a graduate program is fierce. Our objective for this study was to provide prospective graduate students some insights as to what qualifications or attributes would best prepare them for obtaining a graduate position (M.S.) and to excel once they are enrolled in a graduate program. A survey was sent to 50 universities within the National Association of University Fisheries and Wildlife Programs (NAUFWP) where both faculty and undergraduate students were asked questions relating to graduate school. Faculty rated the importance of various criteria and attributes of graduate school, and students answered the questions according to how they believed faculty members would respond. Overall, undergraduate students shared many of the same graduate school viewpoints as those held by faculty members. However, viewpoints differed on some topics related to admittance and the most important accomplishment of a graduate student while enrolled in a graduate program. These results indicate that undergraduate students may be better prepared for graduate school—and they may understand how to be successful once they are enrolled in a program—than was initially thought.